Need to Explore Nanodelivery of Stem Cells with Multimodal Drug like Cerebrolysin for Effective Strategies for Enhanced Neuroprotection and Neurorecovery in Neurodegenerative Disorders - Hari S Sharma; Dafin F Muresanu; José Vicente Lafuente; Ranjana Patnaik; Z Ryan Tian; Asya Ozkizilcik; Herbert Mössler; Aruna Sharma (International Journal of Nanomaterials, Nanotechnology and Nanomedicine - Peertechz Publications, 2016)
Central nervous system (CNS) is vulnerable to various kinds of physical, chemical, metabolic or age-related insults leading to neurodegeneration. Neurodegenerative diseases either caused by aging or following trauma to the CNS results in misery for large number of people across the Globe involving high social costs for them to maintain a good life [1]. Thus, there is an urgent need to find novel solutions to reduce the burden of neurodegenerative disease induced problems in our aging populations. In this context, Alzheimer's disease (AD) is causing huge social burden for the victims as no such therapy available for them to improve their lifetime disabilities [2,3]. This is especially critical to Military personnel who are the victims of brain or spinal cord injuries during combat operations [4]. There are reasons to believe that primary CNS injury could accelerate development of AD or Parkinson's Diseases (PD) over time apart from post-traumatic stress disorders (PTSD) [5]. More often our young victims could also be critical following traumatic injuries to their CNS either following motor vehicle accidents or during combat operations in the battlefield [4]. All these young and old populations require a healthy life.